A Polymer Multilayer Based Amperometric Biosensor for the Detection of Lactose in the Presence of High Concentrations of Glucose. Issue 1 (2nd November 2016) - Lopez, Francesca; Ma, Su; Ludwig, Roland; Schuhmann, Wolfgang; Ruff, Adrian
Abstract: We report on the development of an amperometric polymer multilayer‐based biosensor for the determination of lactose in the presence of high concentrations of glucose. The sensor platform consists of a two‐layer system with the first layer (sensing layer) comprising cellobiose dehydrogenase (CDH) bound by electrostatic interactions in a favourite orientation for efficient direct electron transfer. The second layer on top of the sensing element consists of a specifically designed hydrophilic polymer which co‐entraps glucose oxidase (GOx) and catalase (CAT). This bi‐enzymatic system is able to remove glucose (up to a concentration of at least 140 mM) in the outer layer of the modified electrode and thus prevents the interfering analyte from reaching the active CDH layer. Moreover, the concomitantly generated H2 O2 is efficiently removed by means of CAT. The linear range for the detection of lactose was from 10 to 100 μM. The sensor is able to detect lactose at low concentrations in lactose‐free milk samples. Sample pre‐treatment consist of a simple dilution step. Quantification of the lactose content in lactose‐free dairy products showed that the amount of lactose is below the threshold given by the manufacturer. Abstract :